2006
DOI: 10.2186/prp.5.86
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of In-Ceram Crowns

Abstract: In recent years, the demand for esthetics in restorative dentistry has been increasing. While many allceramic systems have been developed over the years, few long-term clinical data for these systems are available. In this study, we conducted a retrospective clinical evaluation of In-Ceram crowns placed at the Tsurumi University Dental Hospital, at 54 to 64 months after the crown placement. Of the total of 70 In-Ceram crowns fitted, 57 could be followed up. Five crowns were missing, of which two were removed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Until now, the only clinical studies dealing with the longevity of Procera AllCeram crowns have been conducted in Europe (6)(7)(8)(9). In contrast to other studies in Japan involving all-ceramic crown systems, Kokubo et al (10) evaluating 70 In-Ceram crowns showed that their survival rate was 91AE2% after a follow-up exceeding 5 years. In addition, they reported that the cumulative survival rate of 101 In-Ceram crowns with copings fabricated using a computer-aided design ⁄ computer-aided manufacturing system was 93AE9% after 39 months of function (11).…”
Section: Introductionmentioning
confidence: 68%
“…Until now, the only clinical studies dealing with the longevity of Procera AllCeram crowns have been conducted in Europe (6)(7)(8)(9). In contrast to other studies in Japan involving all-ceramic crown systems, Kokubo et al (10) evaluating 70 In-Ceram crowns showed that their survival rate was 91AE2% after a follow-up exceeding 5 years. In addition, they reported that the cumulative survival rate of 101 In-Ceram crowns with copings fabricated using a computer-aided design ⁄ computer-aided manufacturing system was 93AE9% after 39 months of function (11).…”
Section: Introductionmentioning
confidence: 68%
“…The potential for fractures is also present under laboratory conditions. In this report, earlier fracture, which may be related to processing defects, was not observed, and later fractures may be related to fatigue effects, which means that the copings fabricated using the GN‐I system may have fewer processing defects, whereas conventional In‐Ceram crowns had early fractures (11). Two canine crown fractures could have been caused by a fatigue effect applied by guidance during articulation.…”
Section: Discussionmentioning
confidence: 55%
“…All-ceramic crowns are now popular options to restore decayed teeth for both anterior and posterior regions. One of the major systems, the VITA In-Ceram System*, was first introduced in 1989 (1) and has been successfully used as an alternative to conventional porcelainfused-to-metal crowns (2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…This means that the copings fabricated using the GN-I system may have fewer processing defects than conventional In-Ceram crowns that had early fractures. 11 Kelly 33 also reported that the structural durability of all-ceramic crowns is affected by the type of ceramic materials, luting system, and occlusal load.…”
Section: Discussionmentioning
confidence: 99%
“…The In-Ceram system was first introduced in 1990 1 and has been used successfully as an alternative to conventional porcelain-fused-to-metal crowns. [2][3][4][5][6][7][8][9][10][11] Originally, a slip-cast aluminum oxide ceramic was used in In-Ceram crowns. Recently, many computer-aided design/computer-aided manufacturing (CAD/CAM) systems have been developed for use in dentistry.…”
Section: Introductionmentioning
confidence: 99%